Nonopioid Modalities for Acute Postoperative Pain in Abdominal Transplant Recipients. Issue 4 (April 2020) - Chadha, Ryan; Pai, Sher-lu; Aniskevich, Stephen; McClain, Robert; Egan, Brian; Webb, Christopher; Sakai, Tetsuro
Abstract : The field of abdominal organ transplantation is multifaceted, with the clinician balancing recipient comorbidities, risks of the surgical procedure, and the pathophysiology of immunosuppression to ensure optimal outcomes. An underappreciated element throughout this process is acute pain management related to the surgical procedure. As the opioid epidemic continues to grow with increasing numbers of transplant candidates on opioids as well the increase in the development of enhanced recovery after surgery protocols, there is a need for greater focus on optimal postoperative pain control to minimize opioid use and improve outcomes. This review will summarize the physiology of acute pain in transplant recipients, assess the impact of opioid use on post-transplant outcomes, present evidence supporting nonopioid analgesia in transplant surgery, and briefly address the perioperative approach to the pretransplant recipient on opioids.